Association between allergic rhinitis and development of autoimmune thyroid diseases in Egyptian patients - Magdy Mohamed Allam; Soha Magdy Ahmed; Dalia Khamis El-Deeb; Ahmed Yassin Bahgat; Ramy Mohamed Ghazy; Hanaa Tarek El-Zawawy (BMC Endocrine Disorders)
Abstract Background Autoimmune thyroid diseases (AITD) and allergic rhinitis (AR) are prevalent conditions; however, limited research has investigated their association. This study aimed to evaluate whether AR can be considered a risk factor for developing AITD. Methods A retrospective cohort study analyzed the records of AITD patients who visited Alexandria University Students Hospital between January 2017 and December 2021. The parameters included in the study were thyroid-stimulating hormone (TSH), Free triiodothyronine (FT3), free thyroxine (FT4), thyroid peroxidase antibodies (TPOAb), thyrotropin receptor antibody (TRAb), eosinophils count, and IgE. Results Out of 4,515 eligible patients, 41.7% were diagnosed with AR in addition to AITD. Among the patients with both conditions, 81% were females, their mean age was 45.71 ± 24.14 years, and the mean duration of AITD was 7.32 ± 2.11 years. The Kaplan–Meier analysis revealed that the AR cohort had a higher cumulative incidence of AITD than did the non-AR cohort (log-rank test, p = 0.001). Multivariate-adjusted hazardous ratios showed that patients with AR, female sex, higher white blood cell count, and diagnosis in November had a higher risk of developing AITD. Conclusions Screening for AITD should be conducted at the time of diagnosis of AR as it could be a risk factor for AITD.